Antibiotic resistance and determination of resistant genes among cockle (Anadara granosa) isolates of Vibrio alginolyticus - Shahimi, Safiyyah; Elias, Aishah; Abd Mutalib, Sahilah; Salami, Mokry; Fauzi, Fazlina; Mohd Zaini, Nurul Aqilah; Abd. Ghani, Ma'aruf; Ariffin, Ahmad Azuhairi (Springer, 2021)
A total of 24 strains of Vibrio alginolyticus were isolated from cockles (Anadara granosa) and identified for VibA and gyrB genes. All V. alginolyticus isolates were then tested against nine different antibiotics. In this study, the highest percentage of antibiotic resistance was obtained against penicillin (37.50%), followed by ampicillin, vancomycin (12.50%) and erythromycin (8.33%). All of V. alginolyticus isolates were susceptible against streptomycin, kanamycin, tetracycline, chloramphenicol and sulfamethoxazole. Polymerase chain reaction (PCR) assay has confirmed the presence of four antibiotic resistance genes of penicillin (pbp2a), ampicillin (blaOXA), erythromycin (ermB) and vancomycin (vanB). Out of 24 V. alginolyticus isolates, 2 isolates possessed the tdh-related hemolysin (trh) (strains VA15 and VA16) and none for the thermostable direct hemolysin (tdh) gene. Both strains of the tdh-related hemolysin (trh) were susceptible to all antibiotics tested. The multiple antibiotic resistance (MAR) index ranging between 0.2 and 0.3 with 5 antibiograms (A1-A5) was observed. Combination of enterobacterial repetitive intergenic consensus-polymerase chain reaction (ERIC-PCR) and antibiotic resistance indicated 18 genome types which showed genetic heterogeneity of those V. alginolyticus isolates. The results demonstrated the presence of V. alginolyticus strain found in cockles can be a potential risk to consumers and can contribute to the deterioration of human health in the study area. Thus, it is essential for local authority to provide the preventive measures in ensuring the cockles are safe for consumption.